Experimental validation of an accident detection and management application in vehicular environment. (October 2018) - Khaliq, Kishwer Abdul; Raza, Syed Muddasar; Chughtai, Omer; Qayyum, Amir; Pannek, Jürgen
Abstract: Traffic congestion is a common transportation problem around the globe, especially in populated cities, which leads to the issues of traffic safety and its management. A major cause of accidental deaths on the road is due to either the traffic-mismanagement or the absence of quick medical assistance. This work presents a TestBed that is designed and implemented along with the prototype application to provide a solution of traffic safety-and-management using Vehicular Ad hoc Network and Internet-of-Things. The application detects and assesses the severity of accidents with the help of an on-board unit, deployed inside the vehicle. When accident happens, it sends a message to control-room, where a server determines the position of an incident and the nearest hospital to request a quick medical assistance. In order to clear the route to the incident-location, the application in the ambulance generates alert/emergency messages. We analyze the implemented Testbed and evaluate the application for different accident scenarios and conclude that the application detects accidents and assesses the situation correctly to avoid false alarms.